Teachers’ psychological well-being and readiness during covid-19 pandemic in Malaysia - Rosli Suyot; Abu Yazid Abu Bakar; Ifdil Ifdil (RedWhite Press, 2022)
Covid-19 pandemic that hit the whole world including Malaysia had a huge impact on the country's political, economic, social, health, and service system. It also affects the education sector in Malaysia. This pandemic also caused major psychological impacts such as stress, fear, anxiousness, and depression. Therefore, this study was conducted to identify the effect of the COVID-19 pandemic on teachers’ psychological well-being levels and their readiness to handle mental health issues among students. Through these findings, the causative factors of psychological well-being disorders and affected groups can be identified which in turn, can be overcome through appropriate interventions. This study uses an online survey from January 20 to February 13, 2021. To see the level of teachers’ psychological well-being, Depression Anxiety Stress Scale (DASS) instrument was used. A total of 80 teachers (13 males and 67 females) completed this questionnaire. The findings showed that teachers’ psychological well-being is a concern due to many teachers suffering from stress, anxiety, and depression. Therefore, proactive and comprehensive measures need to be carried out by responsible parties such as the Ministry of Education Malaysia so that interventions can be implemented to provide psychological support to educators.